Αμαρτίες, αρρώστιες και γιατρειές στη Μικρά Ασία στους πρώτους μεταχριστιανικούς αιώνες - Χανιώτης Άγγελος (Δελτίο Κέντρου Μικρασιατικών Σπουδών, 1995)
The Greek inscriptions are an important source for the history of ancient medicine. The rows, the reports of miraculous healings, and the confession inscriptions reveal the attitudes of simple people toward illness and cures. This article examines the confession inscriptions of Lydia and Phrygia (2nd-3rd cent. AD), which attest the belief that illness (especially oracular diseases and mental disorders) was a form of divine punishment, usually for a sacrilege. Although scientific medicine was not unknown in these areas, the high costs of medical treatment, the belief in the omnipotence of the local gods, and above all the belief that cure could be attained only through expiation brought the villagers to the local sanctuaries. There, the priests practiced a kind of «religious healing», applying incantations, oracles, sacrifices, purifications, and the ritual transfer of the sin to a triad of animals. In this respect the confession inscriptions of Asia Minor differ from the miraculour healings known from various Asklepieia (Lebena, Epidauros, Pergamon), since the latter are closely related to contemporary scientific medicine.